Clinical InvestigationsA proposed protocol on HDR cylinder treatments: proof of avoidance of re-planning of CT based fractionated treatment, using a critical, statistical and graphical analysis of clinical data - Malik, Sadiq; Banu, Parveen A.; Rukhsana, Naheed; Ahmed, Mushfika; Yasmin, Zebunnesa (Journal of Contemporary Brachytherapy, 2012)
Purpose: An evaluation of CT plan data, using cylinder applicators, in fractionated HDR treatments of cervical cancers has been investigated in this clinical study. Critical and statistical analysis of the data, for each patient and fraction, for plan dose, doses for bladder and rectum have been enumerated and reported. Plans were done for each patient, following CT scans after insertion of the applicator in the respective cases. This process involved time for CT-scan and re-plan, in each fraction, adding cost of treatments for the poor patients. Material and methods : This study on HDR brachytherapy for cervical cancer patients has applied the Co-60 BEBIG Multisource Unit. Cylinder applicators have been applied for treatments. A selection of twenty nine patients, out of a few hundred representative female patients, in the age group of 40-70 years, has been analyzed and presented in this paper. Radiation oncologists inserted the applicator and fixed it in more than 600 treatments. This study, therefore, aimed at their insertion technique, CT-planning by radiation oncology physicists and the delivery of the treatments. Details of set up and technique has been explained, where bladder and rectum doses has been assessed within the tolerance limit [1]. Results : Statistical analysis of data from the treatment plans, substantiates the conclusion of the argument that there is no need to do CT-plans for each subsequently prescribed number of fractions as the doses in plan, bladder and rectum are restricted within the limits of tolerance. Data in Table 1 are analyzed in various graphs. This utilized the Empirical Null Distribution of Group Differences. A graphic study of dose distribution is reported to assure the expected variation of dose from the central tandem. This analysis proves to substantiate a protocol that no re-plan for fractionated delivery is essential following the approval of the first plan. Conclusions : The goal of this study was to critically evaluate the outcome of fractionated cylinder treatments of cervical cancers. This resulted in the set up technique for insertion of applicators and treatment plan, following a CT-scan and the assertion of the argument that re-plans are not necessary for multiple HDR cylinder treatments for the same patient [2,3].